A New National STI and BBV Surveillance System for Aboriginal Community-Controlled Health Services - Ward, James; Bradley, Clare; Donovan, Basil; Hengel, Belinda; Elliott, Salenna (International Journal of Population Data Science, 2020)
Introduction Aboriginal Community-Controlled Health Services (ACCHSs) routinely collect sexually transmissible infection (STI) and blood-borne virus (BBV) clinical data from individuals through electronic medical records (EMRs). At a population level these data are an underutilised resource and can be used to help drive clinical and public health interventions. Accordingly, we have established a national STI and BBV sentinel surveillance network for ACCHSs —the ATLAS network. Objectives and Approach In establishing the ATLAS network, we standardised and automated extraction of deidentified clinical data from multiple EMRs using The University of Melbourne’s GRHANITE™ software. Regular reports are provided to each ACCHS, addressing 12 clinical indicators considered best practice in STI and BBV control and management. Data are used to drive Continuous Quality Improvement strategies, can be aggregated at regional and national levels, and have the ability to link to other surveillance networks also using GRHANITE™. Results The ATLAS network currently includes more than 30 ACCHSs, including urban, regional and remote areas. To date, data have been analysed for >50,000 individuals aged ≥15 years attending medical consultations at ACCHS between January 2016 and December 2018. For clients in the key age-range for STI testing of 15–29 years, the mean annual rate of chlamydia/gonorrhoea testing was 25% (range: 1–59%). The mean annual rate of chlamydia positivity for clients 15–29 years was 3% (range: 0–19%) and the mean annual rate of gonorrhoea positivity was 2% (range: 0–18%). Conclusion / Implications An integrated network of STI and BBV testing and management data has been successfully established amongst ACCHSs nationally. The ATLAS network can be readily expanded and has the potential to link to other datasets using the GRHANITE™ tool. ATLAS provides a unique data infrastructure with capacity to support novel research programs as well as underpin quality improvement activities within participating sites.